Phenomenon of Early Marriage on Girls in The Cintapuri Village in Banjarmasin City (Phenomenological Study) - Lianto Lau, Sherly; Johana, Kornelia; Fannia, Theresi; Rismawaty, Fitria; Awliya, Firda; Ameri, Maya (KnE Social Sciences, 2023)
In this modern era, child marriage still remains a practice in some regions. This phenomenon damages the normal life of families and negatively affects the human capitals of Indonesia. Higher number of child marriages would lead to increase in the divorce rates than normal, as those involved in this marriage have not developed the necessary emotional control for solving problems that might arise during these marriages. This led many to the path of divorce. The goal of this research is to understand the factors that led to child marriage in Cintapuri Village, Banjar Regency, Banjarmasin. This research uses the qualitative descriptive method with phenomenological model. Subjects in this research were teenage girls married in the age of 14-16 with Junior High School (SMP) being their last education level, parents, and village governance apparatus in Cintapuri Village, Banjar Regency, Banjarmasin. The data from this research was collected through careful observations and interviews with people related to the research’s objective. The result of this research shows there are several factors leading to the rampant cases of child marriage, such as economical, educational, and cultural factors. Looked through from an economical point-of-view, many parents are marrying their children off to alleviate their economic burden. From an educational point-of-view, many parents are not aware of the adverse effects of child marriage and the laws that regulate the minimum age of marriage, because of the lack of education. From a cultural point-of-view, parents are feeling nervous and ashamed for the fact that their daughter do not have a partner yet, leading them in search of a suitable partner for their daughter even though their daughter do not always approve of the parent’s suitable partner. Keywords: child marriage, divorce, economy, education, culture